PROBLEMATICHE CONSERVATIVE DEGLI ACQUERELLI NEL RESTAURO - Pelosi, Claudia; Marabelli, Maurizio; Falcucci, Claudio; Giurlanda, Flavio; Ortenzi, Floriana; Patrizi, Francesca (Archeomatica, 2012)
Nelle attività di restauro condotte sulle opere d'arte spesso si utilizzano materiali prodotti dall'industria per altre finalità e che sono entrati nella prassi comune dell'intervento. In particolare il Laboratorio di Diagnostica per la Conservazione e il Restauro "Michele Cordaro”dell'Università della Tuscia di Viterbo ha studiato il comportamento degli acquerelli analizzando le loro caratteristiche chimico-fisiche. Watercolours restoration and conservation issues - Watercolours are today widely used in restoration, especially for the pictorial reintegration thanks to their reversibility and solubility during the time. But these materials show some problem when used in wall painting stored in high relative humidity environment giving rise to colour changes and dripping down the painting surface. The aim of this work has been to study the chemical-physical characteristics of the most used commercial water colours and to test their stability by means of artifi cial aging. Water colour from Maimeri, Windsor&Newton and Talens have been examined; then they have been aged and the colour has been measured to evaluate their changes.